Field relations and petrology of the Trafalgar Plutonic Suite and comparisons with other Devonian granitoid plutons in the Meguma terrane, Nova Scotia, Canada - Puchalski, Raya C.; Barr, Sandra M.; White, Chris E. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2020)
The Trafalgar Plutonic Suite intruded metasedimentary rocks of the Goldenville and Halifax groups in the northeastern part of the Meguma terrane of southern Nova Scotia at about 374 Ma, based on previously published U–Pb and 40Ar/39Ar mineral ages. Using field and petrographic observations, the suite is divided into 20 different plutons on the combined basis of variations in grain size (fine, medium, or coarse), texture (equigranular or porphyritic) and modal mineralogy (quartz diorite/tonalite, granodiorite, monzogranite, and syenogranite). The granodiorite, monzogranite, and syenogranite plutons are relatively uniform in composition with little variation in mineralogy or chemistry within each pluton or between plutons of the same lithology. In contrast the quartz diorite/tonalite plutons show mineralogical and chemical variation, both within and between plutons. The granodiorite, monzogranite, and syenogranite plutons closely resemble other peraluminous granitoid plutons characteristic of the Meguma terrane. The quartz diorite/tonalite plutons are varied but chemically resemble minor Devonian mafic intrusions elsewhere in the Meguma terrane. Like other plutons of the Meguma terrane, the Trafalgar Plutonic Suite has chemical characteristics of volcanic-arc to syn-collisional granitoid rocks and likely has experienced extensive contamination by metasedimentary material as documented by previous studies of plutons in the Meguma terrane. The minor quartz diorite/tonalite plutons are additional examples of the mafic rocks that have been proposed in tectonic models of the Meguma terrane to have facilitated melting of the lower crust to generate granodioritic parent magmas, followed by crystal fractionation and extensive contamination by metasedimentary material.